Wireless Nerve Stimulation via Bioresorbable, Implantable Stimulator for Enhanced Nerve Regeneration. (16th November 2020) - Murthy, Nikhil; D'Andrea, Dominic; Zhao, Jie; Guo, Hexia; Jordan, Sumanas W; Rogers, John; Franz, Colin
Abstract: INTRODUCTION: Peripheral nerve injury (PNI) functional recovery outcomes are incomplete for 90% of patients despite advances in surgical management. The slow and inefficient regeneration of axons is a major reason for poor outcomes. Electrical stimulation (EStim) therapy for augmenting axon regeneration has shown efficacy in both preclinical models and small clinical trials. However, current clinical EStim protocols are impractical due to the barriers created by existing nerve stimulator technology, such as the prohibitively high cost of extending surgical time to deliver EStim intraoperatively, risk for wound infection when patient leaves surgery with transcutaneous wire electrodes left in place, or accidental displacement of transcutaneous wire electrodes. To overcome these barriers, we present data on a novel wireless and bioresorbable nerve stimulator implant system. METHODS: To assess the effectiveness of the wireless, bioresorbable stimulator, mice underwent tibial nerve transection and repair. Immediately post nerve repair mice received supramaximal intensity EStim for 1 hour at 20hz via conventional wired-based or novel implant system, while a third group received sham EStim. The primary outcome was the number of retrogradely labeled neurons 3 weeks post repair. RESULTS: The use of EStim resulted in increased motor neuron reinnervation of the distal nerve after 3 weeks compared to sham control ( P < .05), and the wireless, bioresorbable stimulation device was as effective as the conventional wire-based EStim in both stimulation performance and regeneration outcome. CONCLUSION: The novel wireless and resorbable nerve stimulator implant system described here has the potential to overcome the current practical and technological barriers to implementation of therapeutic EStim in nerve repair.